Implementasi Etika Bisnis Islam Terhadap Keberlangsungan Usaha - Rahmadilla Nurul Fandini Lubis; Nazwa Pirda Aqilla; Mhd Dwi Shandika; Dini Vientiany (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Islamic business ethics is a set of normative principles derived from the Qur'an and Hadith that serve as guidelines for behavior in business activities. These principles emphasize the values of honesty, justice, trustworthiness, and responsibility in every business activity. The application of Islamic business ethics is believed to be oriented not only towards achieving economic profit but also to support sustainable business continuity. This study aims to examine the implementation of Islamic business ethics on business continuity through a theoretical approach. The method used is descriptive qualitative with literature study techniques. The results of the study indicate that internalizing the values of Islamic business ethics can strengthen consumer trust, build a positive business image, and maintain long-term business sustainability. Therefore, Islamic business ethics plays a strategic role in creating sustainable businesses based on moral values.